Estratégias de acessibilidade educacional para e por estudantes com altas habilidades/superdotação - Camargo, Renata Gomes (2013)
Students with High Skills/ Giftedness - AH / SD- are part of the target audience of Special Education that should provide different forms of care for these people, and one of these is the enrichment extraescolar. By analyze the status of education in Brazil, in which the principles of inclusion have been guiding the transformations that are happening in the Brazilian educational system, it is important to study how the attendance in the form of enrichment extraescolar can contribute to the educational accessibility and accessibility and inclusion of these students in school. In this sense, the objective was to understand the strategies of educational accessibility for students with AH/SD, that participating in Extraescolar Enrichment Programs, in view of the same. This research is justified, among other factors, by virtue of that relationship, High Skills/Gifted and educational accessibility, which was held in this investigation was not found in the demand for research and previous publications (CAPES, 2012). Still, the fact is not common to find reference to people with AH / SD in specific documents guiding accessibility in our country. Regarding the methodology, the research was based on a qualitative approach, by assuming a methodological procedure, the case study and data collection tool for the semi- structured interview (GIL, 2010), since the assessment of the data was performed by analysis of content (BARDIN, 2011). As theoretical, studies Freitas and Pérez (2012), Gardner (2010, 2011), Renzulli (2004), Bakhtin (2010), Franchi (2011), among others. In general terms, the main result was that the enrichment programs extraescolar studied and developed several different strategies focused educational accessibility for students with AH/SD, which contribute significantly to the formation of its educational accessibility, as well as for their accessibility and inclusion in school, especially in relation to others, those related to the opportunities and enhancement of expression of AH/SD in different languages.